MEKANISME PENANGANAN PEMBIAYAAN MURABAHAH BERMASALAH Studi pada BMT Syari’ah Pare (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
Problems of  human life is always against the background of  the increasinglydifficult economic conditions. They need help in the form of  funds to accelerateits business, the BMT develop products namely Murabaha financing inaccordance with developments in the banking world and the profit improvementtarget of  the public welfare. Through such financing , financing their sometimesappear problematic because there are several factors, including the inability of customers to pay on time or maturity payments and sometimes the result of  aneffort that substandard and others. This research is qualitative descriptive dataanalysis using primary and secondary data sources with interview techniquesand documentation. Research shows that the causes of  murabaha financingproblems: 1) Analysis of  the lack of  proper financing , 2) Lack or absence of honesty of  customers, 3) the Customer does not actually taking in the operations,4) Business customer experience total bankruptcy, 5) Character from thecustomer itself. As for how to handle the problem of  murabaha financingthat is by identifying the characters from the customer itself, approaching thecustomer later and provide solutions for businesses with examples of  the BMThelp market the products of  its customersMasalah kehidupan manusia selalu dilatarbelakangi kondisi ekonomi yangsemakin sulit. Mereka membutuhkan bantuan dalam bentuk dana untukmempercepat usahanya, BMT mengembangkan produk yaitu pembiayaanMurabahah sesuai dengan perkembangan dunia perbankan dan targetpeningkatan laba dari kesejahteraan masyarakat. Melalui pembiayaan tersebut, pembiayaan mereka terkadang muncul permasalah karena ada beberapa faktor, termasuk ketidakmampuan pelanggan untuk membayartepat waktu atau jatuh tempo pembayaran dan kadang-kadang hasil tidaklancar dan lain-lain. Penelitian ini mendeskripsikan data secara kualitatif dengan menggunakan sumber data primer dan sekunder dengan teknikwawancara dan dokumentasi. Penelitian menunjukkan bahwa penyebabmasalah pembiayaan murabahah: 1) Analisis kurangnya pendanaan yangtepat, 2) Kurangnya atau tidak adanya kejujuran pelanggan, 3) Nasabahtidak benar-benar mengelola dana dalam operasi, 4) pengalaman pelanggandalam kebangkrutan total, 5) Karakter dari pelang gan itu sendiri. Adapuncara untuk menangani masalah pembiayaan murabahah yaitu denganmengidentifikasi karakter dari pelang gan itu sendiri, melakukan pendekatandengan pelanggan dan memberikan solusi untuk berbisnis dengan contoh-contohbantuan pasar produk dari BMT kepada para pelanggan.